2022
DOI: 10.5045/br.2022.2022043
|View full text |Cite
|
Sign up to set email alerts
|

Management of immune thrombocytopenia: 2022 update of Korean experts recommendations

Abstract: Despite the availability of therapies to treat patients with immune thrombocytopenia (ITP), there is currently little data from randomized trials to assist clinicians in managing patients. The evidence-based guidelines of the Korean Society of Hematology Aplastic Anemia Working Party (KSHAAWP) are intended to support patients and physicians in the management of ITP. Experts from the KSHAAWP discussed and described this guideline according to the current treatment situation for ITP in Korea and finalized the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…1). Second, the exclusion criteria were as follows: (1) patients with negative HP infection; (2) those aged < 20 years old; or (3) those with existing comorbidities related to thrombocytopenia, including hepatitis B, hepatitis C, tuberculosis, human immunodeficiency virus disease, thyroid diseases, neoplasms, hematological malignancies, carcinoma in situ, hemorrhagic disorder due to circulating anticoagulants, immunodeficiency, macroglobulinemia, sarcoidosis, rheumatoid arthritis, systemic lupus erythematosus, polymyositis, dermatomyositis, sicca syndrome, systemic sclerosis, vasculitis, antiphospholipid syndrome (abnormal of anti-cardiolipin IgG, B2-Glycoprotein I IgG, and lupus anticoagulant test), and other autoimmune or diffuse connective tissue diseases [4,[8][9][10]. We excluded patients aged < 20 years because we wanted to study adult patients and the adult age was set at 20 years during the study period in Taiwan [11].…”
Section: Study Design Setting and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Second, the exclusion criteria were as follows: (1) patients with negative HP infection; (2) those aged < 20 years old; or (3) those with existing comorbidities related to thrombocytopenia, including hepatitis B, hepatitis C, tuberculosis, human immunodeficiency virus disease, thyroid diseases, neoplasms, hematological malignancies, carcinoma in situ, hemorrhagic disorder due to circulating anticoagulants, immunodeficiency, macroglobulinemia, sarcoidosis, rheumatoid arthritis, systemic lupus erythematosus, polymyositis, dermatomyositis, sicca syndrome, systemic sclerosis, vasculitis, antiphospholipid syndrome (abnormal of anti-cardiolipin IgG, B2-Glycoprotein I IgG, and lupus anticoagulant test), and other autoimmune or diffuse connective tissue diseases [4,[8][9][10]. We excluded patients aged < 20 years because we wanted to study adult patients and the adult age was set at 20 years during the study period in Taiwan [11].…”
Section: Study Design Setting and Patientsmentioning
confidence: 99%
“…HP, Helicobacter pylori; HPE, Helicobacter pylori eradication therapy. *Other possible diseases that may cause thrombocytopenia: hepatitis B, hepatitis C, tuberculosis, human immunodeficiency virus disease, hyperthyroidism, hypothyroidism, thyroiditis, simple and unspecified goiter, non-toxic nodular goiter, thyroid diseases, neoplasms, hematological malignancies, carcinoma in situ, neoplasm of uncertain behavior of other lymphatic and hematopoietic tissues, hemorrhagic disorder due to circulating anticoagulants, immunodeficiency, macroglobulinemia, sarcoidosis, rheumatoid arthritis, systemic lupus erythematosus, polymyositis, dermatomyositis, sicca syndrome, systemic sclerosis, vasculitis, antiphospholipid syndrome (abnormal of anti-cardiolipin IgG, B2-Glycoprotein I IgG, and lupus anticoagulant test), and other autoimmune or diffuse connective tissue diseases [4,[8][9][10] were performed to investigate the effect modification. Furthermore, we performed multivariate logistic regression analyses to identify independent predictors of ITP in the patients with HP infection.…”
Section: Statisticsmentioning
confidence: 99%
“…Apart from the Spanish 10 and Japanese 11 recommendations, with splenectomy clearly positioned as third-line treatment, most other countries, in accordance with the US recommendations and the international consensus, place splenectomy, rituximab and TPO-RAs at the same level as second-line treatment, with personalized treatment according to the patient's characteristics and wishes. [12][13][14][15][16] Evolution of the therapeutic strategy in 'real life' Analysis of real-life practices shows that the recommendations of the guidelines are rarely respected. In Spain, Lozano et al 17 showed that splenectomy is performed very early and a very early use of TPO-RAs during the course of ITP, in contradiction to international recommendations.…”
Section: Evolution Of the Guidelinesmentioning
confidence: 99%
“…Initial treatment of newly diagnosed ITP is recommended at a platelet count <20–30×10 9 /L in adult patients without symptoms [ 5 - 7 ]. The experts also recommended that treatment goals should be individualized to each patient and aimed at both preventing bleeding as well as minimizing toxicity and optimizing quality of life [ 6 ].…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Corticosteroids: The preferred first-line therapy for patients with chronic ITP is oral corticosteroids, unless there is a contraindication to corticosteroids or need for more rapid platelet increase due to acute bleeding. Most-commonly used corticosteroids are oral prednisone at 0.5–2 mg/kg/day for 2–3 weeks and should be tapered aiming to stop by 6–8 weeks [ 5 - 7 ]. Initial response rates range from 70 to 80%, but relapse rates are high and long-term remission rates are low [ 8 ].…”
Section: Current Treatmentsmentioning
confidence: 99%